Analysis of Public Ownership and Management Ownership on the Implementation of the Triple Bottom Line in the Plantation Sector Listed on the Indonesia Stock Exchange - Saut Maruli Tua Pandiangan; Fida Oktafiani; Santi Rohdearni Panjaitan; Mutiara Shifa; Riny Jefri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this research is to find out and analysis of public ownership and management ownership on the implementation of the triple bottom line in the Plantation Sector listed on the Indonesia Stock Exchange. This research was conducted through quantitative research. The type of data to be collected is secondary data. The sample in this study were 15 companies in the plantation sector. The data analysis technique used in this study used descriptive statistical analysis and panel data regression. The regression data panel consists of determination coefficient (R2) test, simultaneous (F) test, and partial (t) test. The results showed that determination coefficient (R2) test that public ownership and management ownership together are able to explain the implementation of the triple bottom line in the Plantation Sector listed on the Indonesia Stock Exchange. The simultaneous (F) test shows that public ownership and management ownership simultaneously have a significant effect on the implementation of the triple bottom line in the Plantation Sector listed on the Indonesia Stock Exchange. The partial (t) test shows that public ownership partially has a significant effect on the implementation of the triple bottom line in the Plantation Sector listed on the Indonesia Stock Exchange and management ownership partially has a unsignificant effect on the implementation of the triple bottom line in the Plantation Sector listed on the Indonesia Stock Exchange.